2020
DOI: 10.3847/1538-4357/abafad
|View full text |Cite
|
Sign up to set email alerts
|

Cool, Luminous, and Highly Variable Stars in the Magellanic Clouds from ASAS-SN: Implications for Thorne–Żytkow Objects and Super-asymptotic Giant Branch Stars

Abstract: Stars with unusual properties can provide a wealth of information about rare stages of stellar evolution and exotic physics. However, determining the true nature of peculiar stars is often difficult. In this work, we conduct a systematic search for cool and luminous stars in the Magellanic Clouds with extreme variability, motivated by the properties of the unusual Small Magellanic Cloud star and Thorne-Żytkow Object (TŻO) candidate HV 2112. Using light curves from ASAS-SN, we identify 38 stars with surface tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 196 publications
1
5
0
Order By: Relevance
“…Motivation: Our goal in this paper was to clarify the nature of a population of sAGB star candidates identified by O'Grady et al (2020), and to see if any evidence supported a TŻO identity for any of the stars. We investigated their kinematics, local SFH, and radio properties.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation: Our goal in this paper was to clarify the nature of a population of sAGB star candidates identified by O'Grady et al (2020), and to see if any evidence supported a TŻO identity for any of the stars. We investigated their kinematics, local SFH, and radio properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although no ECSN progenitors have been observationally confirmed, some candidate populations have been proposed which, if validated, would help to constrain the nature of ECSNe in single stars (O'Grady et al 2020). Hiramatsu et al (2021) propose that SN 2018zd was an ECSN from a single sAGB star based on the low energy and chemical profile of the light curve.…”
Section: Discussionmentioning
confidence: 99%
“…Levesque et al (2014) identified a chemical anomaly in a supergiant star HV2112 in Small Magellanic Cloud (Worley et al 2016;McMillan & Church 2018) which is consistent with a TŻO (Tout et al 2014). It is also suggested that HV2112 may be an asymptotic-giant-branch star rather than a TŻO (Tout et al 2014;Beasor et al 2018;O'Grady et al 2020). There are ongoing observational efforts to discover TŻOs (DeMarchi et al 2021).…”
Section: Introductionmentioning
confidence: 91%